2002
DOI: 10.1177/0163278702025001005
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Handsearching European General Health Care Journals to the Cochrane Controlled Trials Register

Abstract: A fundamental aim of any systematic review is that all relevant studies should be identified and considered for inclusion. Limitations with searching bibliographic databases led the Cochrane Collaboration to search journals by hand for reports of trials. This article presents the results of a 3-year project to identify and make accessible reports of randomized trials published in European general health care journals. Overall, 21,620 reports of controlled trials were identified from 119 journals from 16 countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Limitations with searching bibliographic databases led the Cochrane Collaboration to search European general health-care journals by hand for reports of controlled trials: only 17% of those identified were indexed in MEDLINE as controlled trials and 30% were not indexed in MEDLINE at all. 110 Accordingly, a multipronged approach is currently advocated: searching a range of databases; hand-searching of relevant journals; contacting experts in the field of enquiry for curricula vitae and information; and examination of the 'grey literature' , conference proceedings and the like. Decisions have to be made at each stage depending on the resources available.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations with searching bibliographic databases led the Cochrane Collaboration to search European general health-care journals by hand for reports of controlled trials: only 17% of those identified were indexed in MEDLINE as controlled trials and 30% were not indexed in MEDLINE at all. 110 Accordingly, a multipronged approach is currently advocated: searching a range of databases; hand-searching of relevant journals; contacting experts in the field of enquiry for curricula vitae and information; and examination of the 'grey literature' , conference proceedings and the like. Decisions have to be made at each stage depending on the resources available.…”
Section: Introductionmentioning
confidence: 99%
“…where publishing is not the primary activity of the producing body’ [48,49]. Related research has assessed the value of handsearching for trials [50-52] and examined the characteristics associated with full publication of meeting abstracts [53]. Alternative search techniques such as 'pearl-growing’/'snowballing’ from known key references and checking reference lists have also been explored [54,55].…”
Section: Information Retrieval Methods: Celebrating the First 20 Yearmentioning
confidence: 99%
“…"Canadian Journal of Emergency Medicine", "Journal Européen des Urgences" oder "Emergency Medicine") führte zu einzelnen, zum Teil relevanten RCTs [28]. [27].…”
Section: Methodikunclassified